Alfabetização de jovens e adultos na agenda internacional: os princípios político-pedagógicos da UNESCO nos guias práticos para a educação extraescolar (1960-1966) - Souza, Luana Aparecida Lourenço De (2020)
Bearing in mind the relationship between history and identity, interrogating the past to expand knowledge about the history of EJA is a way to (re)affirm the identity of the modality as a pedagogical field and therefore, as a research field. In these terms, this study analyzed the didactic-methodological perspective contained in the Practical Guides for Extra-School Education published by UNESCO in the 1960s, in order to understand the pedagogical principles that defined the objectives and the means conveyed by this international agency for the Literacy for youth and adults. The methodology of this research is based on Carlo Ginzburg's conception of the indicative paradigm, where through the clues and minutiae of details, it is possible to decipher an enigma, by elucidating a plot and revealing a secret. This with the contribution of Dario Ragazzini on the use of documentary sources in studies of the history of education. For the author, sources play an important role in history and have a three-tier construction process: the one who produced the source, the one who observes and preserves it, and the one who will deepen its content and conduct research on it. As one of the basic foundations of cultural history, the entire research process was carried out considering the social, political and cultural context of the period, that is, the context being crossed with the data extracted from the source. As a result, the examination of the sources indicated that there was a convergence between the issues of adult literacy addressed at the II International Conference on Adult Education and the didactic-methodological guidelines contained in the Practical Guides for Extra-School Education. The use of audiovisual resources, adoption of active and participatory methods, consideration of the influence of the media on the cultural formation of individuals, the need for qualified teachers, the provision of financial resources for teacher training, for the acquisition and preparation of teaching materials and facilities for the meetings, the need for literacy campaigns mainly in developing countries and the importance of the contribution of developed countries to carry out these campaigns are examples of approximations between II International Conference on Adult Education and the content of the Practical Guides for Extra-School Education. In addition, permanent education, markedly aimed at professionalization, was also present in the discussions and guidelines of both. In short, adult education was seen as a way to organize the capitalist mode of production and as a way to ensure peace between peoples. This research also made it possible to understand UNESCO as a civilizing institution, in the sense that, when publishing the collection, it sought to occupy a place that radiates adult literacy models to be adopted by its member countries.